Impact of working capital management on corporate Profitability: Evidence from capital goods companies Listed on CSE - Mithila, G.; Kabishka, T. (University of Jaffna, 2025)
The study employs fixed effect model, random effect and pooled OLS to understand the impact between variables and fixed model is selected as appropriate to analyse variables. Operating Profit Margin (OPM) is the dependent variable while Cash Conversion Cycle (CCC), Days Inventory Outstanding (DIO), Days Sales Outstanding (DSO), Days Payables Outstanding (DPO), Current Ratio (CA) are considered as the independent variables with control variables such as AGE, SIZE and Leverage (LEV). The findings reveal that higher DIO reduces profitability, while better management of DPO and CR positively impacts OPM. Larger firms benefit from economies of scale and better liquidity enhances profitability. The study also DSO and firm age do not directly affect the profitability, suggesting that other factors, like cost management might be more critical. Additionally, LEV does not show a significant impact on profitability, emphasizing the need for cautions debt structuring. These insights provide practical guidance for financial managers in optimizing working capital management to enhance firm performance. Academics and researchers can also leverage the findings of this study for future research. Additionally, regulatory bodies should establish a robust framework to ensure the smooth functioning of firms.
Keywords: Capital Goods Companies; Profitability; Liquidity; Working Capital Management